Persistent bias in advice-giving - Zhuoqiong Chen; Tobias Gesche (University of Zurich, Department of Economics, 2017)
We show that a one-off incentive to bias advice has persistent effects. In an experiment, some advisers were paid a bonus to recommend a lottery which only risk-seeking individuals should choose to a less informed client. Afterwards, they had to choose for themselves and make a second recommendation to another client, without any bonus. These advisers choose the risky lottery and recommend it a second time up to six times more often than advisers in a control group who were never offered a bonus. These results are consistent with a theory we present which is based on advisers' image concerns of appearing incorruptible.
Keywords: C91; D03; D83; G11; 330; advice-giving; conflict of interest; self-signaling; self-deception